2018
DOI: 10.31703/gssr.2018(iii-iii).19
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Direct Anti-Smoking Public Service Advertisements and Anti-Smoking Messages Placement Disclosures in Movies with Attitude to Quit Smoking

Abstract: Recently, the Ministry of Health Pakistan decreed that disclosures of anti- smoking messages placement in the movies should be used whereby fear based cognitive anti-smoking message is shown. Consistent with the Elaboration Likelihood Model (ELM) assumption that persuasion messages likely influence the attitude of the relatively unmotivated individuals. This study is the first which tests and compare the ability of anti-smoking persuasion messages presented in the Direct Anti-smoking public service Advertiseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Hsieh et al [21,22] showed that anti-cigarette campaigns positively impact the knowledge and perception of harm, which was negatively associated with smoking behaviors. Similarly, studies have shown that anti-cigarette information conveyed through various sources such as television, movie theaters, and similar sources can positively shape anti-cigarette attitudes among the viewers [23][24][25].…”
Section: Introductionmentioning
confidence: 97%
“…Hsieh et al [21,22] showed that anti-cigarette campaigns positively impact the knowledge and perception of harm, which was negatively associated with smoking behaviors. Similarly, studies have shown that anti-cigarette information conveyed through various sources such as television, movie theaters, and similar sources can positively shape anti-cigarette attitudes among the viewers [23][24][25].…”
Section: Introductionmentioning
confidence: 97%